2021
DOI: 10.1155/2021/9996305
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Emphysema Index Combined with the Chronic Obstructive Pulmonary Disease Assessment Test Score in the Evaluation of Chronic Obstructive Pulmonary Disease

Abstract: Background. This study aimed to evaluate the efficacy of the emphysema index (EI) in distinguishing chronic bronchitis (CB) from chronic obstructive pulmonary disease (COPD) and its role, combined with the COPD Assessment Test (CAT) score, in the evaluation of COPD. Methods. A total of 92 patients with CB and 277 patients with COPD were enrolled in this study. Receiver operating characteristic (ROC) curves were analyzed to evaluate whether the EI can preliminarily distinguish chronic bronchitis from COPD. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Predictors are defined as physiological parameters that can change based on the body’s physiology, such as the ROX index, which is calculated using SpO 2 and respiratory rate. A recently published study ( 37 ) demonstrated that the HACOR scale can be a highly effective tool for predicting NIV failure in non-COPD patients receiving NIV. It was also reported ( 38 ) that the HACOR scale can be useful for predicting NIV failure in hypoxic patients with respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors are defined as physiological parameters that can change based on the body’s physiology, such as the ROX index, which is calculated using SpO 2 and respiratory rate. A recently published study ( 37 ) demonstrated that the HACOR scale can be a highly effective tool for predicting NIV failure in non-COPD patients receiving NIV. It was also reported ( 38 ) that the HACOR scale can be useful for predicting NIV failure in hypoxic patients with respiratory failure.…”
Section: Discussionmentioning
confidence: 99%